Beliefs about Prophet Isa in Islam: a critical refutation of Mirza Ghulam Ahmad's claims in the light of Qur'an and Sunnah - Ahmad, Khalil; Ali, Mohammed Farid; Abiodun, Abdul Ganiyi Muhammad Raji (IIUM Press, International Islamic University Malaysia, 2017)
This paper looks into some of the claims made by Mirza Ghulam Ahmad Qadiyani against the Prophet Isa (as). Mirza’s claims were not only discourteous to Isa (as), but were also not in line with the fundamental beliefs propagated by Islam. The Qur’an and Sunnah has emphasized Isa’s Prophet-hood, his reverence, his miracles, his ascending and his descending as the promised messiah. The mainstream SunnÊ School namely the Ahl Sunnah wa al-Jama'ah base their position on these deliberations. Early tafsir works such as Ibn Jarir al-Tabari’s Tafsir al-Tabari, al-Nasafi’s Madarik al-Tanzil wa Haqa’iq al-Ta’wil, and major hadith sources are referred to in exposing the mainstream position of Islam and concomitantly refuting Mirza’s claims.